1999
DOI: 10.1034/j.1399-3003.1999.14d18.x
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide among pulpmill workers reporting gassing incidents involving ozone and chlorine dioxide

Abstract: The aim of the study was to investigate whether measurement of nitric oxide in exhaled air could be used for assessing the effects of irritants on the respiratory system, in this case recurrent ozone gassing in an occupational setting.The study population comprised bleachery workers (n=56) from a Swedish pulpmill carrying out ozone-based pulp bleaching since 1992 and controls (n=39). Both groups were investigated by measuring NO in exhaled air, methacholine challenge test and answers to a questionnaire concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
16

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 27 publications
(30 reference statements)
0
25
0
16
Order By: Relevance
“…There is a longitudinal study from Quebec, Canada, showing that Cl 2 gassings increase airway responsiveness [26,27]. OLIN and coworkers [28][29][30] found increased nitric oxide in exhaled air among bleachery workers reporting ozone gassings, which may indicate chronic airway inflammation. Irritants are known to trigger inflammation through epithelial injury, but it has also been proposed that neuronal activity through neuropeptides gives rise to, and maintains, inflammation (i.e.…”
Section: Asthma Irritants and Gases E Andersson Et Almentioning
confidence: 99%
“…There is a longitudinal study from Quebec, Canada, showing that Cl 2 gassings increase airway responsiveness [26,27]. OLIN and coworkers [28][29][30] found increased nitric oxide in exhaled air among bleachery workers reporting ozone gassings, which may indicate chronic airway inflammation. Irritants are known to trigger inflammation through epithelial injury, but it has also been proposed that neuronal activity through neuropeptides gives rise to, and maintains, inflammation (i.e.…”
Section: Asthma Irritants and Gases E Andersson Et Almentioning
confidence: 99%
“…Follow-up began for all the workers in 1992 and continued until either 1996 or the year of reported onset of rhinitis, whichever came first. Additional information on selection of the participants can be found elsewhere (4,5).…”
Section: Study Population and Methodsmentioning
confidence: 99%
“…Workers are sometimes exposed to these gases at high levels due to accidental leakage. Several studies have shown an increase in lower respiratory symptoms due to these accidental gassings (2)(3)(4)(5). In addition, Olin et al (4) reported an increase in exhaled nitric oxide, which indicates possible respiratory inflammation, after exposure to ozone gassings.…”
mentioning
confidence: 99%
“…Each subject performed at least three technically acceptable trials, and the largest values for FVC and FEV1 were retained and compared with predicted values [18]. Details of spirometry measurements are documented in previous studies [14,15]. Each subject's average annual changes in FEV1 (DFEV1), FVC (DFVC), and FEV1/FVC (DFEV1/FVC) were calculated using the following equation:…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…In a study at one Swedish pulp mill, investigators found increased exhaled nitric oxide among bleachery workers reporting ozone gassings, suggesting airways inflammation may have been present [14]. The investigators also reported that the forced expiratory volume in one second (FEV1) was lower for bleachery workers compared with process workers from the adjacent paper mill (97.6% versus 104.0% predicted; p50.007), while there was no difference between the two groups in forced vital capacity (FVC) [14]. When comparisons were limited to the bleachery workers, those who reported ozone gassings did not have lower FEV1 or FVC.…”
mentioning
confidence: 99%